2010
DOI: 10.2989/1814232x.2010.501591
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of sardine caught by the beach-seine fishery during the KwaZulu-Natal sardine run

Abstract: Catches of sardine Sardinops sagax made by the beach-seine fishery off the KwaZulu-Natal (KZN) coast during the annual winter sardine run have been sampled intermittently since 1951, and a substantial amount of data on various biological characteristics of sardine caught off KZN now exists. Information on length frequency distributions, mean caudal length (CL), length-mass relationships, condition factor (CF), age distributions, sex ratio, gonad maturity and diet have been collated and are presented in this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Published and unpublished information on biological characteristics of sardine from the west and south coast collected from commercial catch and research survey samples was collated by van der Lingen et al . (2009) in order to examine whether spatial variability in these characteristics occurred and, if so, whether such provided plausible evidence for the existence of two stocks. Sardine condition factor (calculated as the ratio of observed to expected wet body mass) showed significant spatial variation, with fish from east of Cape Agulhas showing higher condition factor values than those from the west coast (van der Lingen et al .…”
Section: Studies Of South African Sardine Population Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Published and unpublished information on biological characteristics of sardine from the west and south coast collected from commercial catch and research survey samples was collated by van der Lingen et al . (2009) in order to examine whether spatial variability in these characteristics occurred and, if so, whether such provided plausible evidence for the existence of two stocks. Sardine condition factor (calculated as the ratio of observed to expected wet body mass) showed significant spatial variation, with fish from east of Cape Agulhas showing higher condition factor values than those from the west coast (van der Lingen et al .…”
Section: Studies Of South African Sardine Population Structurementioning
confidence: 99%
“…Subsequent analyses of vertebral count and body shape data from sardine collected from South Africa's east coast showed that fish from this region had significantly fewer vertebrae and a different body shape compared with those from the west or south coasts (van der Lingen et al . 2010 b ).…”
Section: Studies Of South African Sardine Population Structurementioning
confidence: 99%
See 3 more Smart Citations